A magnetic flux rope configuration derived by optimization of two-spacecraft In-situ measurements - Hu, Qiang; He, Wen; Chen, Yu (Frontiers in Physics, 2022)
Increasingly one interplanetary coronal mass ejection (ICME) structure can propagate across more than one spacecraft in the solar wind. This usually happens when two or more spacecraft are nearly radially aligned with a relatively small longitudinal separation angle from one another. This provides multi-point measurements of the same structure and enables better characterization and validation of modeling results of the structures embedded in these ICMEs. We report such an event during October 13-14, 2019 when the Solar TErrestrial RElations Observatory Ahead (STA) spacecraft and the Parker Solar Probe (PSP) crossed one ICME structure at two different locations with nominal separations in both heliocentric distances and the longitudinal angles. We first perform an optimal fitting to the STA in-situ measurements, based on an analytic quasi-three dimensional (3D) model, yielding a minimum reduced $χ^2=0.468$. Then we further apply the optimization approach by combining the magnetic field measurements from both spacecraft along their separate paths across the ICME structure. We find that the output based on the optimization (with the minimum reduced $χ^2=3.15$) of the combined two-spacecraft dataset yields a more consistent result, given the much improved agreement of the model output with PSP data. The result demonstrates a magnetic flux rope configuration with clear 3D spatial variations.